2006
DOI: 10.1521/jscp.2006.25.6.603
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Self–Regulatory Efficacy Beliefs in Managing Affect and Family Relationships to Positive Thinking and Hedonic Balance

Abstract: In line with prior work, the present study aimed at examining a conceptual model that assigns a crucial role to affective and family interpersonal self-regulatory efficacy beliefs in influencing the cognitive and affective components of subjective well-being, namely, positive thinking and hedonic balance. Positive thinking is posited as the latent dimension underlying life satisfaction, self-esteem, and optimism. In contrast, hedonic balance is posited as the difference between positive affect and negative aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
44
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 91 publications
13
44
0
1
Order By: Relevance
“…In accordance with previous studies (Alessandri et al, submitted for publication;Caprara & Steca, 2005, 2006aCaprara et al, 2006;Steca et al, 2009), the current contribution presents news findings attesting to a latent dimension common to life satisfaction, self-esteem, and optimism. Results from the first study demonstrated that individuals' positive life-and self-evaluations and future expectations share a latent component that likely reflects a common mode of positively viewing life, oneself and expected experiences.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with previous studies (Alessandri et al, submitted for publication;Caprara & Steca, 2005, 2006aCaprara et al, 2006;Steca et al, 2009), the current contribution presents news findings attesting to a latent dimension common to life satisfaction, self-esteem, and optimism. Results from the first study demonstrated that individuals' positive life-and self-evaluations and future expectations share a latent component that likely reflects a common mode of positively viewing life, oneself and expected experiences.…”
Section: Discussionsupporting
confidence: 92%
“…These findings corroborate previous results [15,16] pointing to the contribution that emotional and social self-efficacy beliefs may exert on strengthening major expressions of positive orientation. Yet the more people draw, from experience, their beliefs to be able to properly handle their emotions and their relations with others, the more they can preserve and enhance a positive evaluation of self, life and the future.…”
supporting
confidence: 91%
“…Moreover, earlier studies have demonstrated the contribution of emotional and social self-efficacy to positive orientation [15,16] . However, the contribution of positive orientation to self-efficacy beliefs was not directly assessed.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In the future, it will be important to investigate the degree to which other factors such as optimism, self-esteem, life satisfaction, and the inclusion of enrichment activities in daily life help to explain the relationship between positive aspects of caregiving and self-efficacy (Caprara & Steca, 2006;Carbonneau et al, 2010;Gottlieb & Rooney, 2004).…”
Section: Aging and Mental Health 685mentioning
confidence: 99%